A comparative study of 3 alternative avian toxicity testing methods: Effects on hepatic gene expression in the chicken embryo. (4th October 2019) - Mittal, Krittika; Crump, Doug; Basu, Niladri
Abstract: There is growing interest in developing alternative methods to screen and prioritize chemical hazards, although few studies have compared responses across different methods. The objective of the present study was to compare 3 alternative liver methods derived from white Leghorn chicken ( Gallus gallus domesticus ): primary hepatocyte culture, liver slices, and liver from in ovo injected embryos. We examined hepatic gene expression changes after exposure to 3 chemicals (17β‐trenbolone [17βT], 17β‐estradiol [E2], and 2, 3, 7, 8‐tetrachlorodibenzo‐ p ‐dioxin [TCDD]) using a custom quantitative polymerase chain reaction (qPCR) array with 7 genes (vitellogenin [VTG], apolipoprotein [Apo], cytochrome P450 1A4 [CYP1A4], liver basic fatty acid binding protein [LBFABP], 3β hydroxysteroid dehydrogenase [HSD3β1], stearoyl coenzyme A desaturase [SCD], and estrogen sulfotransferase [SULT1E1]). Gene expression across the 3 methods was examined using hierarchical clustering. Up‐regulation of CYP1A4 in response to TCDD was consistent across all methods, and the magnitude was higher in hepatocytes (>150‐fold) compared with slices (>31‐fold) and in ovo liver (>27‐fold). In hepatocytes, SCD and VTG up‐regulation in response to 17βT and E2 was >4‐fold and 16‐fold, respectively. The rank order of cases with significant changes in gene expression among the 3 methods was: hepatocytes (22) > in ovo liver (11) > liver slices (6). Hierarchical clustering grouped liver slices and in ovo liver as more similar, whereas hepatocytes were grouped separately from in ovo liver. More introspective comparisons are needed to understand how and why alternative methods differ and to aid in their integration into toxicity testing. Environ Toxicol Chem 2019;38:2546–2555. © 2019 SETAC